Cr3+ substitution effect on Co-Cu and Cu-Co nano ferrites on structural and morphological properties - Parajuli, D.; Murali, N.; Samatha, K. (BIBECHANA, 2023)
The Cr3+ substituted Co-Cu (Co0.7Cu0.3Fe2-xCrxO4) and Cu-Co (Cu0.7Co0.3Fe2-xCrxO4) where x = 0.0, 0.05, 0.1, 0.15, 0.2 and 0.25 nano ferrite composite were prepared with the sol-gel approach. Their structural, dc electrical resistivity, and magnetic properties were analyzed. XRD shows the single-phase spinel ferrite. Adding Cr3+ ions decreases the lattice volume and the size of the crystallite respectively. FESEM images show non-spherical particles on a largely uniform surface shape with decreasing grain size on doping Cr3+. The FTIR pattern supports the XRD patterns for spinel ferrite.